Do We Optimize Vitamins and Folic Acid Treatment in Dialysis Patients? New and Old Challenges - Ashikova, Krasimira Atanasova; Kolev, Nikola (International Journal For Research In Health Sciences And Nursing, 2020)
SUMMARY: It has been known for many years that the administration of Folic acid (FA) and Vitamin B12 is a necessary replacement therapy for chronic renal failure patients on periodic hemodialysis due to a number of dietary restrictions in these patients. There is a lot of writing, talking and research about Vitamin B12 and FA deficiency. However, there are only sporadic publications on Vitamin B12 and FA hypervitaminosis and its consequences. ABOPHOLIC META is available in Bulgaria since 2011, and it has been used in the Dialysis Department at Sveta Anna Hospital, Sofia ever since. It is noteworthy that during the years of use of this preparation, using additional amounts of Vitamin B12 is becoming rarer and in fewer patients. The purpose of this follow-up is to: Determine whether patients maintain stable (within the reference range) serum levels of Vitamin B12 and FA during a 6-month period of ABOPHOLIC META administration. Confirm the hypothesis of a real difference (association) between the outcomes in patients with good compliance of both sexes. Material and methods: 57 dialysis patients were followed up in the Dialysis Department at UMHAT “Sveta Anna”, Sofia. Hemoglobin, Vitamin B12 and FA results were compared. The methods of prospective follow-up and the following Data analyses were used: t-Test: Two-Sample Assuming Unequal Variances, Descriptive statistics: point estimates of parameters-finding of averages, Deductive statistics, Parametric analysis. Abbott Diagnostics’ CLIA Aliniy ci-series was used as the method of testing of Vitamin B12 and FA serum levels. Hemoglobin was tested by a colorimetric method. Conclusions: At a dose of ABOPHOLIC META 1 tab/day, the patients maintained stable Vitamin B12 and FA serum levels and no further Vitamin B12 containing preparation was required. There were no patients with FA level above the reference range. There was a real difference (association) between the results of patients of both sexes with good compliance for both Folic acid (P-value = 0.030) and Vitamin B12 (P-value = 0.032). No similar data on available sex differences are reported in the scientific literature. This is the first time this has been proven in those patients.